Bela Negara in Islamic Frame to Realize The Vision Of Indonesia Emas 2045 - Muhammad Zulham; Muhammad Rifqi Romadhona (Universitas Nasional, 2021)
This paper takes the topic of Bela Negara to achieve the vision of 2045 in the frame of Islam. The vision of Indonesia Emas 2045 is an overview of Indonesia's demographic bonus in the 2045 period will be challenged. Bela negara is an attitude and behavior that is imbued by citizens because of his love for the Republic of Indonesia based on Pancasila and the 1945 Constitution to ensure and realize the survival of the nation and state. The objectives of State Defense can be seen more clearly and deeply from a defensive perspective against threats, distractions, obstacles and challenges (AGHT). With the Islamic point of view about defending the state giving this view is a form of obedience to Allah SWT to achieve a just and prosperous society. This view will be a strong spirit for the community, especially for young people to achieve the vision of Indonesia Emas 2045.Keywords: Bela Negara, Islam, Vision of Indonesia Emas 2045